An Interventionist and Psychometrician Considers Assessing Changes in Spiritual Formation - Worthington, Everett L. (Journal of spiritual formation & soul care, 2021)
There are two parts to this present article. First, I consider the applied problem of assessing changes in a congregation—how often to assess, why assess, what changes are looked for, what interventions are assessed, why look to the components of interventions, and how to avoid problems interpreting your data. Brief assessments are mandatory. Pastors and lay leaders can make simple but sound assessments of their spiritual formation programs using item response theory, goal attainment scales, single items, parceling single items, or narrative responses as five alternatives. I describe dangers in interpreting the findings such as not knowing the base rate of change and mistaking the assessment for the mission. In the second part of the article, I briefly describe a program labeled a deep dive into humility. I summarize the assessments that were done, which gives a practical example of the technical recommendations I made earlier in the article.